Remodeling of the Neurovascular Unit Following Cerebral Ischemia and Hemorrhage - Yoshimichi Sato; Jaime Falcone-Juengert; Teiji Tominaga; Hua Su; Jialing Liu (Cells, 2022)
Formulated as a group effort of the stroke community, the transforming concept of the neurovascular unit (NVU) depicts the structural and functional relationship between brain cells and the vascular structure. Composed of both neural and vascular elements, the NVU forms the blood–brain barrier that regulates cerebral blood flow to meet the oxygen demand of the brain in normal physiology and maintain brain homeostasis. Conversely, the dysregulation and dysfunction of the NVU is an essential pathological feature that underlies neurological disorders spanning from chronic neurodegeneration to acute cerebrovascular events such as ischemic stroke and cerebral hemorrhage, which were the focus of this review. We also discussed how common vascular risk factors of stroke predispose the NVU to pathological changes. We synthesized existing literature and first provided an overview of the basic structure and function of NVU, followed by knowledge of how these components remodel in response to ischemic stroke and brain hemorrhage. A greater understanding of the NVU dysfunction and remodeling will enable the design of targeted therapies and provide a valuable foundation for relevant research in this area.